Relative effects of human capital, social capital and psychological capital on hotel employees’ job performance - Huang, Songshan (Sam); Yu, Zhicheng; Shao, Yuhong; Yu, Meng; Li, Zhiyong (International journal of contemporary hospitality management, 2021)
Purpose This study examines the relative effects of human capital (HC), social capital (SC) and psychological capital (PC) on hotel employees’ job performance. Design/methodology/approach A sample of 417 employees from seven five-star hotels in China was recruited for the study. Both exploratory and confirmatory factor analyses were used to confirm the quality of measurement structures. Stepwise regression was used to examine the relative effects of the three capitals on hotel employees’ job performance. Findings PC was found to be the strongest predictor of self-reported job performance (SJP) among the three capitals under investigation. Education and work experience in the HC domain affected SJP, whereas SC dimensions did not. However, only education and work experience in the HC domain were found to affect supervisor-rated job performance (RJP). Practical implications Given the impact of PC on hotel employee’s SJP, human resource managers should attend to this capital in staff recruitment, retention and training and development. Originality/value This study provides a holistic comparative lens to examine the relative contribution of the three capitals on hotel employees’ job performance. This will help to further clarify the roles played by each of the capitals in hotel service work, thus advancing the development of the theories underlying each of the three capitals.